Impacto de polimorfismos de genes do metabolismo do folato e do microRNA hsa-mir-149 no risco para cardiopatias congênitas em indivíduos com síndrome de Down - Santos, Mariana Fernanda (2016)
Congenital heart defects (CHD) are present in approximately 40 to 60% of individuals with Down syndrome (DS). It is the leading cause of death in the first years of life in individuals with the syndrome. Polymorphisms in maternal and fetal genes encoding enzymes involved in folate metabolism have been associated with the development of congenital heart defects. Objectives: To assess if the presence of polymorphism (MTHFR rs4846048, MTHFR rs4846049, hsa-mir-149 rs2292832, MTHFR C677T, MTHFR A1298C, MTHFR T1317C, MTR A2756G, MTRR A66G, SLC19A1 A80G, TC2 A67G, TC2 C776G, CßS 844ins68, CßS T833C, MTHFD1 G1958A, BHMT G742A, DHFR del 19 pb, and SHMT C1420T) in individuals with DS is associated with the occurrence of CHD in these individuals. We also evaluated the association between maternal genetic polymorphisms MTHFR rs4846048, MTHFR rs4846049 and hsa-mir-149 rs2292832, and the presence of CHD in offspring with DS. Methods: This study included 139 individuals (80 individuals with DS and CHD, and 59 control subjects with DS without congenital heart disease). Molecular analysis of MTHFR rs4846048, MTHFR rs4846049 and hsa-mir-149 rs2292832 was carried out by real time polymerase chain reaction allelic discrimination. Genotyping data of MTHFR C677T, MTHFR A1298C, MTHFR T1317C, MTR A2756G, MTRR A66G, SLC19A1 A80G, TC2 A67G, TC2 C776G, CßS 844ins68, CßS T833C, MTHFD1 G1958A, BHMT G742A, DHFR del 19 pb, and SHMT C1420T were obtained from database of previous studies of the research group and also used to assess the risk for the occurrence of CHD in this study. Multiple logistic regression analyzes were performed to assess the risk of CHD in the presence of 17 polymorphisms in dominant and recessive genetic models. The median number of mutant alleles between groups was assessed by the Mann-Whitney test. Genotypic combination analysis was performed for the polymorphisms MTHFR rs4846048, MTHFR rs4846049, and hsa-mir-149 rs2292832, using Fisher's exact test, dominant model. Results: Multiple logistic regression analysis involving individuals with DS showed no association between 17 polymorphisms and the risk for CHD. The median number of polymorphic alleles did not differ among individuals with DS with and without CHD. On the other hand, the maternal genotypes hsa-mir-149 rs2292832 CT or TT were associated with reduced risk for isolated heart disease in the offspring (OR = 0,31; 95% CI = 0,13 to 0,72; P = 0,0063). The analysis of genotypic combinations of MTHFR rs4846048, MTHFR rs4846049, and hsa-mir-149 rs2292832 in individuals with DS, and their mothers showed no association between the different combinations and the risk for congenital heart disease. Conclusions: There is no evidence of association between the polymorphisms analyzed in individuals with DS and the occurrence of CHD. However, a lower risk of isolated congenital heart disease for individuals with DS is observed in the presence of maternal genotypes hsa-mir-149 rs2292832 CT or TT.